The social life of nanotechnology - Harthorn, Barbara Herr, 1951-; Mohr, John. (New York : Routledge, 2012)
"This volume shows how nanotechnology takes on a wide range of socio-historically specific meanings in the context of globalization, across multiple localities, institutions and collaborations, through diverse industries, research labs, and government agencies and in a variety of discussions within the public sphere itself. It explores the early origins of nanotechnologies; the social, economic, and political organization of the field; and the cultural and subjective meanings ascribed to nanotechnologies in social settings. "--
pt. I. Constructing the field of nanotechnology: the social origins of nanotechnology -- pt. II. Controlling the field: the role of public policies, market systems, scientific labor, and globalization in nanotechnology -- pt. III. Contesting the field: knowledge, power, and reflexivity in the construction of nanotechnology.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nanotechnology -- Social aspects; Electronic books